Role of Crotonyl Coenzyme A Reductase in Determining the Ratio of Polyketides Monensin A and Monensin B Produced by Streptomyces cinnamonensis - Liu, Haibin (American Society for Microbiology, 1999)
The ccr gene, encoding crotonyl coenzyme A (CoA) reductase (CCR), was cloned from Streptomyces cinnamonensis C730.1 and shown to encode a protein with 90% amino acid sequence identity to the CCRs of Streptomyces collinus and Streptomyces coelicolor. A ccr-disrupted mutant, S. cinnamonensis L1, was constructed by inserting the hyg resistance gene into a unique BglII site within the ccr coding region. By use of the ermE* promoter, the S. collinus ccr gene was expressed from plasmids in S. cinnamonensis C730.1/pHL18 and L1/pHL18. CCR activity in mutant L1 was shown to decrease by more than 90% in both yeast extract-malt extract (YEME) medium and a complex fermentation medium, compared to that in wild-type C730.1. Compared to C730.1, mutants C730.1/pHL18 and L1/pHL18 exhibited a huge increase in CCR activity (14- and 13-fold, respectively) in YEME medium and a moderate increase (3.7- and 2.7-fold, respectively) in the complex fermentation medium. In the complex fermentation medium, S. cinnamonensis L1 produced monensins A and B in a ratio of 12:88, dramatically lower than the 50:50 ratio observed for both C730.1 and C730.1/pHL18. Plasmid (pHL18)-based expression of the S. collinus ccr gene in mutant L1 increased the monensin A/monensin B ratio to 42:58. Labeling experiments with [1,2-(13)C(2)]acetate demonstrated the same levels of intact incorporation of this material into the butyrate-derived portion of monensin A in both C730.1 and mutant C730.1/pLH18 but a markedly decreased level of such incorporation in mutant L1. The addition of crotonic acid at 15 mM led to significant increases in the monensin A/monensin B ratio in C730.1 and C730.1/pHL18 but had no effect in S. cinnamonensis L1. These results demonstrate that CCR plays a significant role in providing butyryl-CoA for monensin A biosynthesis and is present in wild-type S. cinnamonensis C730.1 at a level sufficient that the availability of the appropriate substrate (crotonyl-CoA) is limiting.